Potamophylax idliri sp. nov. (Trichoptera: Limnephilidae), a new species from the Jastrebac Mountains in Serbia, with molecular and ecological notes - Ibrahimi, Halil; Bilalli, Astrit; Kučinić, Mladen; Hlebec, Dora; Gashi, Agim; Kotori, Linda Grapci; Stojanović, Katarina; Živić, Ivana (Zootaxa, 2022)
In this paper, we describe a new species, Potamophylax idliri sp. nov., from the Jastrebac Mountains in Serbia, which is morphologically most similar to Potamophylax coronavirus Ibrahimi, Bilalli & Vitecek 2021 (in Ibrahimi et al. 2021) and Potamophylax juliani Kumanski 1999 (in Kumanski & Malicky 1999). The males of the new species differ from all known species of the Potamophylax winneguthi Species Group by morphological characters of the male genitalia. The genetic distinctiveness calculated based on sequencing of the barcode region of the cytochrome c oxidase subunit I gene (COI) between Potamophylax idliri sp. nov. and other species of the Potamophylax winneguthi Species Group is on par with those of other morphologically recognized species in the group and especially the other four species of the P. winneguthi Species Cluster. Potamophylax winneguthi Species Cluster is erected for the following species: P. idliri sp. nov., P. winneguthi, P. haidukorum Malicky 1999 (in Kumanski & Malicky 1999), P. juliani, and P. coronavirus, characterized primarily by the bilobed apical margins of inferior appendages with pointed corners, in lateral and caudal views. The new species was found at two localities in the Jastrebac Mountains, at 988 and 891 m above sea level. Considering the knowledge about distribution and ecology of the other species of this group, we posit that P. idliri sp. nov. is a microendemic of the Jastrebac Mountains in Serbia.